Genetic resources and traditional knowledge : case studies and conflicting interests - Bubela, Tania; Gold, E. Richard (Cheltenham, UK : Edward Elgar Pub., 2012)
This fascinating study describes efforts to define and protect traditional knowledge and the associated issues of access to genetic resources, from the negotiation of the Convention on Biological Diversity to The Declaration on the Rights of Indigenous Peoples and the Nagoya Protocol. Drawing on the expertise of local specialists from around the globe, the chapters judiciously mix theory and empirical evidence to provide a deep and convincing understanding of traditional knowledge, innovation, access to genetic resources, and benefit sharing. Because traditional knowledge was understood in ear.
Includes bibliographical references and index.
Keywords: Germplasm resources -- Economic aspects; Law; Agriculture; Intellectual property (International law); Traditional ecological knowledge -- Law and legislation -- Case studies; Germplasm resources conservation -- Case studies